Aplikasi Pembelajaran Kidung Bali Berbasis Android (Studi Kasus: Desa Bali Agung Lampung Selatan) - Ayu Melia Santi; Machudor Yusman; Made Widhiyana; Irwan Adi Pribadi (Jurnal Pepadun, 2022)
Technology is a tool used to facilitate human work. With technology, humans can obtain information from various parts of the world and can be connected to one another with individuals or groups. In the teachings of Hinduism, the Kidung is a song or sacred chant that is specifically sung during the implementation of religious ceremonies. Kidung can be done by everyone to give praise to Ida Sang Hyang Widhi Wasa. The very rapid development of technology at this time makes the Learning Application Kidung can be used as a medium to increase the desire to learn in adolescents or adults, especially in the Village of Bali Agung who really do not understand how to develop Balinese Kidung. This research has succeeded in developing this application which successfully displays 13 kidung, including, 3 (three) Song of Dewa Yajña, 2 (two) Song of Butha Yajña, 3(three) Song of Pitra Yajña, 3 (three) Song of Manusa Yajña, 1 (one) The Song of Rsi Yajña. This application runs on the Android operating system so that it can be accessed by anyone and at any time on a smartphone or tablet computer that supports the Android operating system. The conclusion of this research is that the Android-based Kidung Bali Learning Application has been successfully built and has been tested to match the expected results.